Changes in older adults' life space during lung cancer treatment: A mixed methods cohort study. Issue 1 (5th October 2021) - Wong, Melisa L.; Shi, Ying; Smith, Alexander K.; Miaskowski, Christine; Boscardin, W. John; Cohen, Harvey Jay; Lam, Vivian; Mazor, Melissa; Metzger, Lia; Presley, Carolyn J.; Williams, Grant R.; Loh, Kah Poh; et al.
Abstract: Background: Maintenance of function during cancer treatment is important to older adults. Characteristics associated with pretreatment life‐space mobility and changes during non‐small cell lung cancer (NSCLC) treatment remain unknown. Methods: This mixed methods cohort study recruited adults age ≥65 with advanced NSCLC starting palliative chemotherapy, immunotherapy, and/or targeted therapy from a Comprehensive Cancer Center, Veterans Affairs, and safety‐net clinic. Patients completed geriatric assessments including Life‐Space Assessment (LSA) pretreatment and at 1, 2, 4, and 6 months after treatment initiation. LSA scores range from 0 to 120 (greater mobility); LSA <60 is considered restricted. We used mixed‐effects models to examine pretreatment LSA, change from 0 to 1 month, and change from 1 to 6 months. A subgroup participated in semistructured interviews pretreatment and at 2 and 6 months to understand the patient experience of life‐space change. For each interview participant, we created joint displays of longitudinal LSA scores juxtaposed with illustrative quotes. Results: Among 93 patients, median age was 73 (range 65–94). Mean pretreatment LSA score was 67.1. On average, LSA declined 10.1 points from pretreatment to 1 month and remained stable at 6 months. Pretreatment LSA score was associated with several demographic, clinical, geriatric assessment, and symptom characteristics. LSA decline at 1 month was greater among patients with high anxiety (slope = −12.6 vs. −2.3, p  = 0.048). Pretreatment body mass index <21 kg/m 2 was associated with LSA improvement from 1 to 6 months (slope = 4.1 vs. −0.04, p  = 0.003). Joint displays illustrated the impact of different life‐space trajectories on patients' lives in their words. Conclusion: Older adults with NSCLC have low pretreatment life space with many developing restricted life space during treatment. Incorporating life‐space assessments into clinical cancer care may help older adults concretely visualize how treatment might impact their daily function to allow for informed decision making and identify early changes in mobility to implement supportive interventions.